Normative and Practical Distinction Between Ijarah, 'Ariyah, Hiwalah, And Qard: A Comparative Study of Muamalah Fiqh in Indonesia - Rifai, Ahmad; Jubaedah, Dedah; Setiawan, Iwan (Zona Law And Public Administration Indonesia, 2026)
This study aims to analyze the normative and practical differences between the four main contracts in fiqh muamalah, namely ijarah (rent-benefit), 'ariyah (borrowing goods without compensation), hiwalah (debt transfer), and qard (voluntary loan). Normatively, the four contracts have a strong foundation in classical fiqh literature, but their practice in Indonesia shows different variations and challenges. The research uses a qualitative field approach with in-depth interviews and observations on the community and Islamic financial institutions, especially BMT, KJKS, and Islamic banks. The results of the study show that there is a gap between normative fiqh and the reality of the field. Ijarah contracts are widely developed in Islamic financial institutions, but some people still equate them with buying and selling. Akad 'ariyah is more dominant in daily social interactions, reflecting the value of helping, although it is rarely understood as part of the fiqh of muamalah. Hiwalah contracts have been found to be very limited, although they have great potential to support modern transactions similar to debt transfer mechanisms in conventional finance. Meanwhile, qard contracts are still popular both in the social and institutional realms, but in practice they are often confused with interest-bearing loans so that they risk deviating from sharia principles. This study concludes that the low sharia literacy of the community and the limitation of product innovation in financial institutions are the main factors that cause the gap between norms and practices. Therefore, public education, intensive socialization, and the development of innovative products based on muamalah contracts are needed so that the concept of classical fiqh is not only a normative reference, but also functions as a real instrument in building the Islamic economy in Indonesia